Thai version of the Survey Instrument for Natural History, Aetiology and Prevalence of Patellofemoral Pain: Cross-cultural validation and test-retest reliability - Wannaporn Sumranpat Brady; Yodchai Boonprakob; Thooptong Kwangsawad; Athawit Buahong; Pongthorn Asawaniwed; Nuttapong Khachornsaengcharoen; Michael Callaghan; James Selfe (Elsevier, 2021)
Background: /objective: The Survey Instrument for Natural History, Aetiology and Prevalence of Patellofemoral Pain (SNAPPS) is a self-report questionnaire which is a specifically designed measurement instrument to identify patellofemoral pain. It has reported high sensitivity, specificity and test-retest reliability to discriminate between people with knee pain, with or without patellofemoral pain. SNAPPS hasn't been studied in Thailand; therefore, the aim of this study was to cross-culturally adapt the questionnaire into Thai. Method: This study was separated into two phases: cross-cultural adaptation and test-retest reliability. The Survey Instrument for Natural History, Aetiology and Prevalence of Patellofemoral Pain was translated into Thai following the guidelines for the cross cultural adaptation of self-report measures including six steps. Thirty four knee pain patients performed the test-retest reliability of the final version of this questionnaire. They were clinically diagnosed with patellofemoral pain by a physical therapist. They were asked to complete the questionnaire twice; with the 1st session and 2nd session having a 30 min break between. The intraclass correlation coefficient (ICC3, 1) method was used to determine test-retest reliability. The correlation of SNAPPS and VAS-U, VAS-W, VAS-S, VAS- J, VAS- R, and VAS- SQ were analyzed by Pearson correlation. Results: The thirty-four participants (19 males, 15 females; with ages ranging 19-24 years) with patellofemoral pain were assessed twice with a 30 min break between the two sessions. The total scores of section 2 and 4 of the questionnaire indicated very strong test-retest reliability, ranging from 0.83 to 0.954 and the total score was ICC 0.91. Moreover, the Survey Instrument for Natural History, Aetiology and Prevalence of Patellofemoral Pain had a correlation with intensity of pain during ascending and descending stairs. Conclusion: The Thai version of the Survey Instrument for Natural History, Aetiology and Prevalence of Patellofemoral Pain can be used to assess patellofemoral pain in young Thai patients.